Determinants of low birth weight: a systematic review - Annisa Arum Shinta Dewi; Koekoeh Hardjito; Finta Isti Kundarti (International Journal of Health Science and Technology, 2022)
More than 80% of neonatal deaths that occur in newborns are caused by Low Birth Weight (LBW). This increases the risk of several health problems, such as susceptibility to infections, chronic non-communicable developmental diseases, and growth and intellectual disability that may occur during infancy, childhood, and the later stages of life. Therefore it is necessary to reduce the prevalence of LBW to achieve Sustainable Development Goals (SDGs). The purpose of this study was to determine the determinants of LBW through a systematic review. The method used in the systematic review study was searching through the Pubmed, ProQuest, and Science Direct databases with the year of publication from January 2012 to January 2022. The results of almost all articles were obtained, which said that the mother’s nutritional status, maternal age, anemia, hypertension of pregnancy, parity, ANC, and smoking affect LBW. Two factors greatly influence the seventh factor: the ANC visit factor and the mother's nutritional status. It is essential to regularly check for pregnancy as early as possible so it can be detected early. Health workers can also monitor the growth and development of the fetus, as well as the importance of fulfilling balanced nutrition during pregnancy.